Diagnostic of competitiveness of the producer sector of Arracacia xanthorrhiza Bancroft. Case municipality of Boyacá (Colombia) 2014 - Rojas Cruz, Diana Lizeth; Barreto Bernal, Patricia Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article analyzes the competitiveness of the production sector of Arracacia xanthorrhiza Bancroft in the municipality of Boyacá, and its influence on the territory. For this purpose, “Five Forces” and “Diamond of competitiveness” models, developed by Professor Michael Porter, are employed.The results obtained allowed establishing a qualitative assessment of the current situation and prospects of the chain, clarifying key factors that should be improved for generating value propositions and opportunities aimed at building alternatives in agribusiness, which facilitate access to new markets and provide both sustainable growth for the region as a better quality of life for farmers.